Citotaxonomia de espécies de Cactaceae ocorrentes no nordeste do Brasil - Castro, Juliana Pereira de (2012)
Were studied with CMA3 and DAPI fluorochrome staining techniques and in situ hybridization with 45S and 5S rDNA probes, representatives of the subfamilies Pesreskioideae, Opuntioideae and Cactoideae, 28 species of 14 genera, occurring mainly in the Northeast of Brazil, aiming to identify the heterochromatin distribution and location of rDNA sites in these species and their taxonomic implications. In the subfamilies Pereskioideae and Opuntioideae, chromosome numbers range from 2n = 22 in Pereskia aculeata, P. bahiensis, P. grandiflora (Pereskioideae), Brasilopuntia brasiliensis, Tacinga funalis and T. palmadora, 2n = 44 O. dillenii and 2n = 88 in O. ficus-indica (Opuntioideae). All species presented symmetric karyotypes and small chromosomes, with average sizes range from 1.94 μm in O. dillenii to 3.17 μm in P. aculeata. A pair of terminal CMA+ bands corresponding to the NORs occurred in all cytotypes in diploid and also O. dillenii (tetraploid), except in O. ficus-indica (octoploid) that exhibited two pairs of terminal bands. Additional CMA bands were observed in the interstitial region in the long arm of B. brasiliensis chromosome pair, while a variable number of pericentromeric bands were seen in three chromosome pairs in O. dillenii and in the majority of chromosomes in O. ficus-indica. The sites of 45S rDNA bands corresponded to the terminal CMA, while 5S sites were located in the interstitial region of a chromosome pair in P. aculeata, P. bahiensis and P. grandiflora, as in B. brasiliensis the 5S site was subterminal. In the subfamily Cactoideae, there were no previous chromosome records for Arrojadoa, Micrathocereus and Pilosocereus genera, as in Melocactus azureus, M. levitestatus, Stephanocereus luetzelburgii, Discocactus zehntneri, Hylocereus setaceus and Harrisia adscendens. In Arrojadoa, data for chromosome CMA+ banding pattern does not support inclusion of A. aurespina in A. rodantha limits. In Melocactus and Pilosocereus genera, there was a wide numeric variation of CMA+ pericentromeric bands, while CMA+ bands corresponding to the NORs were generally corresponding to the ploidy level. In species where 45S rDNA sites were mapped, there was a complete correspondence with the terminal CMA+ bands, and there were no additional 45S sites. Moreover, 5S sites were extremely variable in number and chromosomal location. 5S sites adjacent to 45S sites were characteristic of all Pilosocereus species analyzed. The variability in the number and distribution of CMA+ bands and 5S sites location were important cytotaxonomic characteristics in the studied taxa delimitation.